Treadmill Exercise Decreases Aβ Deposition and Counteracts Cognitive Decline in APP/PS1 Mice, Possibly via Hippocampal Microglia Modifications - Zhang, Xianliang; He, Qiang; Huang, Tao; Zhao, Na; Liang, Fei; Xu, Bo; Chen, Xianghe; Li, Tuojian; Bi, Jianzhong (Frontiers in Aging Neuroscience, 2019)
Recent studies have suggested that exercise may be beneficial for delaying or attenuating Alzheimer’s disease (AD). However, the underlying mechanisms were not clear. Microglia-mediated neuroinflammation is suggested to play an important role in the pathology of AD. The present study investigated the beneficial effects of treadmill exercise on amyloid-β (Aβ) deposition and cognitive function in amyloid precursor protein (APP)/PS1 mice in the early stage of AD progression and microglia-mediated neuroinflammation was mainly analyzed. The results demonstrated that 12 weeks of treadmill exercise preserved hippocampal cognitive function in APP/PS1 mice and substantially suppressed Aβ accumulation in the hippocampus. Treadmill exercise significantly inhibited neuroinflammation, which was characterized by a remarkably reduced expression of pro-inflammatory factors and increased expression of anti-inflammatory mediators in the hippocampus, resulting from a shift in activated microglia from the M1 to M2 phenotype. Treadmill exercise also attenuated oxidative stress presented by a marked reduction in methane dicarboxylic aldehyde (MDA) level and dramatically elevated SOD and Mn-SOD activities in the hippocampus. These findings suggest that treadmill exercise can effectively prevent the decrease in hippocampal-dependent cognitive function and Aβ deposits in early AD progression possibly via modulating microglia-mediated neuroinflammation and oxidative stress.